Restoration of Finishing of Russian Neoclassical Furniture. Myths and Realities - Torbik, Vladimir S. (Actual Problems of Theory and History of Art, 2015)
Furniture constantly requires restoration interventions. However, old technologies are so far insufficiently studied. The lack of knowledge about old techniques and finishing materials leads to a significant change in color and texture of wood after restoration. This paper is a timely contribution to the research in this field. Based on literature and archive materials, laboratory and practical studies, it reveals the difference in meaning of the terms ‘polishing’ and ‘varnishing’ in 19th century and today and offers a related description of the relevant processes. The techniques associated with the terminology are described. The key value of the natural oils and pumice stone for polishing furniture is stressed. The author reaches a conclusion that the use of oil and pumice as furniture polish proves to be an essential part of the process. The results of the study should form the basis for the restoration methods of polishing of Neoclassical furniture and help to save the initial artistic image of historic furniture.